A controlled solvothermal synthesis of CuS hierarchical structures and their natural-light-induced photocatalytic properties. (20th May 2015) - Hosseinpour, Zahra; Alemi, Abdolali; Khandar, Ali Akbar; Zhao, Xiujian; Xie, Yi
Abstract : A solvothermal synthesis of CuS hierarchical structures for the photodegradation of methylene blue (MB). Abstract : Hierarchical structures of covellite CuS are successfully prepared by a facile one-step solvothermal approach using CuCl2 ·2H2 O and sodium thiosulfate as the copper and sulfur precursors, respectively. The as-synthesized self-assembly hierarchical structures are characterized by using powder X-ray diffraction (XRD), field emission-scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), UV-vis-NIR spectroscopy and photoluminescence (PL) spectra. The experimental XRD patterns and HRTEM confirm the formation of a hexagonal structure of covellite CuS. The solvent volume ratios of ethylene glycol (EG) to ethanol (ET) are revealed to play a critical role in the morphology control of the hierarchical structures. The photocatalytic activity of the resulting CuS photocatalysts is investigated by the degradation of the organic methylene blue (MB) under natural light irradiation, which suggests much higher photoactivity of the CuS hierarchical structures than that of commercial CuS and TiO2 photocatalysts.